Welcome to Moldy Manor - Stilton, Geronimo (Scholastic Inc., 2015)
"Rancid rat hairs! I'd been spending so much money lately, I had none left in the bank! Even worse, when my grandfather found out, he sent me off to Moldy Manor. There, miserly Uncle Stingysnout would teach me to be better at saving. How terrible! Could I learn to be less wasteful without going crazy?" --